Português para principiantes - Albuquerque, Severino J. (Open textbook library., 2016)
Português para principiantes is a time-tested text which can be used in conjunction with a variety of approaches to the teaching of beginning Portuguese. This media-rich text is designed to provide learners with a solid grammatical basis for using Brazilian Portuguese as well as regular opportunities to practice and improve their ability to read, speak, and understand the Portuguese language as it is used in contemporary Brazil.